High Performance Building Facade Solutions: PIER Final Project Report - Eleanor S. Lee; Stephen E. Selkowitz; Dennis L. DiBartolomeo; Joseph H. Klems; Robert D. Clear; Kyle S. Konis; Robert J. Hitchcock; Mehry Yazdanian; Robin Mitchell; Maria Konstantoglou (2009)
Building façades directly influence heating and cooling loads and indirectly influence lighting loads when daylighting is considered, and are therefore a major determinant of annual energy use and peak electric demand. façades also significantly influence occupant comfort and satisfaction, making the design optimization challenge more complex than many other building systems. This work focused on addressing significant near-term opportunities to reduce energy use in California commercial building stock by a) targeting voluntary, design-based opportunities derived from the use of better design guidelines and tools, and b) developing and de ploying more efficient glazings, shading systems, daylighting systems, façade systems and integrated controls. This two-year project, supported by the California Energy Commission PIER program and the US Department of Energy, initiated a collaborative effort between The Lawrence Berkeley National Laboratory (LBNL) and major stakeholders in the façades industry to develop, evaluate, and accelerate market deployment of emerging, high-performance, integrated façade solutions. The LBNL Windows Testbed Facility acted as the primary cata lyst and mediator on both sides of the building industry supply-user business transaction by a) aiding component suppliers to create and optimize cost effective, integrated systems that work, and b) demonstrating and verifying to the owner, designer, and specifier community that these integrated systems reliably deliver required energy performance. An industry consortium was initiated amongst approximately seventy disparate stakeholders, who unlike the HVAC or lighting industry, has no single representative, multi-disciplinary body or organized means of communicating and collaborating. The consortium provided guidance on the project and more importantly, began to mutually work out and agree on the goals, criteria, and pathways needed to attain the ambitious net zero energy goals defined by California and the US. A collaborative test, monitoring, and reporting protocol was also formulated via the Windows Testbed Facility in collaboration with industry partners, transitioning industry to focus on the import ance of expecting measured performance to consistently achieve design performance expectations. The facility enables accurate quantification of energy use, peak demand, and occupant comfort impacts of synergistic façade-lighting-HVAC systems on an apples-to-apples comparative basis and its data can be used to verify results from simulations. Emerging interior and exterior shading technologies were investigated as potential near-term, low-cost solutions with potential broad applicability in both new and retrofit construction. Commercially-available and prototype technologies were developed, tested, and evaluated. Full-scale, monitored field tests were conducted over solstice-to-solstice periods to thoroughly evaluate the technologies, uncover potential risks associated with an unknown, and quantify performance benefits. Exterior shading systems were found to yield net zero energy levels of performance in a sunny climate and significant reductions in summer peak demand. Automated interior shading systems were found to yield significant daylighting and comfort-related benefits. In support of an integrated design process, a PC-based commercial fenestration (COMFEN) software package, based on EnergyPlus, was developed that enables architects and engineers to x quickly assess and compare the performance of innovative façade technologies in the early sketch or schematic design phase. This tool is publicly available for free and will continue to improve in terms of features and accuracy. Other work was conducted to develop simulation tools to model the performance of any arbitrary complex fenestration system such as common Venetian blinds, fabric roller shades as well as more exotic innovative façade systems such as optical louver systems. The principle mode of technology transfer was to address the key market barriers associated with lack of information and facile simulation tools for early decisionmaking. The third party data generated by the field tests and simulation data provided by the COMFEN tool enables utilities to now move forward toward incentivizing these technologies in the marketplace.

Innovative Façade Systems for Low-energy Commercial Buildings - Eleanor S. Lee; Stephen E. Selkowitz; Dennis L. DiBartolomeo; Joseph H. Klems; Robert D. Clear; Kyle S. Konis; Maria Konstantoglou; Mark Perepelitza (Lawrence Berkeley National Laboratory, 2009)
Glazing and façade systems have very large impacts on all aspects of commercial building performance. They directly influence peak heating and cooling loads, and indirectly influence lighting loads when daylighting is considered. In addition to being a major determinant of annual energy use, they can have significant impacts on peak cooling system sizing, electric load shape, and peak electric demand. Because they are prominent architectural and design elements and because they influence occupant preference, satisfaction and comfort, the design optimization challenge is more complex than with many other building systems. Façade designs that deliberately recognize the fundamental synergistic relationships between the façade, lighting, and mechanical systems have the potential to deliver high performance over the life of the building. These "integrated" façade systems represent a key opportunity for commercial buildings to significantly reduce energy and demand, helping to move us toward our goal of net zero energy buildings by 2030. Provision of information — technology concepts, measured data, case study information, simulation tools, etc. — can enable architects and engineers to define integrated façade solutions and draw from a wide variety of innovative technologies to achieve ambitious energy efficiency goals. This research is directed toward providing such information and is the result of an on‐going collaborative research and development (R&D) program, supported by the U.S. Department of Energy and the California Energy Commission Public Interest Energy Research (PIER) program.

Simulating Complex Window Systems Using BSDF Data - Maria Konstantoglou; Jacob C. Jonsson; Eleanor S. Lee (26th Conference on Passive and Low Energy Architecture (PLEA), June-22-24, 2009)
Nowadays, virtual models are commonly used to evaluate the performance of conventional window systems. Complex fenestration systems can be difficult to simulate accurately not only because of their geometry but also because of their optical properties that scatter light in an unpredictable manner. Bi-directional Scattering Distribution Functions (BSDF) have recently been developed based on a mixture of measurements and modelling to characterize the optics of such systems. This paper describes the workflow needed to create then use these BSDF datasets in the Radiance lighting simulation software. Limited comparisons are made between visualizations produced using the standard ray-tracing method, the BSDF method, and that taken in a full-scale outdoor mockup.